Examination of the Relationship Between Perceived Freedom Levels in Leisure Time and Multidimensional Leadership Orientations of Individuals Engaged in Nature Sports as a Recreational Activity - Koç, Kenan; Yüce, Mustafa Soner; Ulucan, Hakkı; Serarslan, Mustafa Zahit; Usufcan, Oğulcan; Kir, Sevim; Kırık, Erdal; Yüce, Mustafa Soner; Serarslan, Mustafa Zahit (Frontiers, 2025)
Introduction:The purpose of this study is to examine the relationship betweenperceived freedom in leisure and multifaceted leadership orientations amongindividuals engaged in recreational nature sports residingin various provincesof the Central Anatolia region.Methods:In this study, a quantitative research method was used. The sampleconsisted of 633 randomly selected volunteers from Kayseri, Kýr ̧sehir, andNev ̧sehir. Data collection instruments included the “Multifaceted LeadershipOrientations Scale”, “Perceived Freedom in Leisure Scale”, and demographicinformation form. Participants’ personal information, inventory scores, and factorscores were presented using frequency (f) and percentage (%) values. Forcomparing scale scores, independentt-test statistics were used for gender andmarital status variables, while one-way analysis of variance (LSD) was employedfor age, educational status, sports discipline, duration of engagement in naturesports, and welfare level comparisons. Pearson correlation analysis (r) wasapplied to determine the relationship between the scores obtained from thescales.Results:The research findings indicate that individuals participating inrecreational nature sports activities exhibit high levels ofperceived freedom inleisure and average levels of leadership orientation. On the other hand, analysis ofvarious variables revealed significant differences between perceived freedom inleisure time and marital status, sport discipline, and years ofparticipation, as wellas between the some sub-dimensions of multifaceted leadership orientationsand gender, marital status, education level, age, sport discipline, years ofparticipation, and welfare level.Discussion:The correlation analysis revealed a strong positive relationshipbetween perceived freedom in leisure levels and multifaceted leadershiporientations. This positive correlation is thought to stem from individuals’ desireto prioritize their own wishes, emotions, and ideas to feel freeduring their leisuretime.
Keywords: Recreation; Nature sports; Perceived freedom; Leadership; Leisuretime